A novel throttling strategy for adiabatic compressed air energy storage system based on an ejector - Chen, Long Xiang; Hu, Peng; Zhao, Pan Pan; Xie, Mei Na; Wang, Dong Xiang; Wang, Feng Xiang (Energy conversion and management, 2018)
•A novel throttling strategy is proposed for adiabatic compressed air energy storage.•The throttling strategy is based on an ejector.•Proposed energy storage system is more efficient and economic than the conventional one.•The performance of ejector is stable and hardly affected by the ambient. Adiabatic compressed air energy storage presents a valuable and environmentally friendly option for massive energy storage. Currently, efficiencies are approximately 70%, in part due to the issue of exergy losses during the air throttling. To enhance the performance of the system, a novel adiabatic compressed air energy storage is proposed using a new throttling strategy with an additional ejector. The compressed air in the storage vessels has been divided into three parts with different pressures. The part of compressed air with highest pressure is regarded as primary fluid of ejector to compress the part of air with lowest pressure in the other storage vessel to an intermediate pressure. Hence the inlet pressure of high pressure turbine enhanced, results in the system efficiency improves. The thermodynamic analysis including energy analysis, exergy analysis and the parametric analysis are evaluated by using steady-state mathematical model and thermodynamic laws. The calculations show that the round trip efficiency improves nearly 2% and the profit increases by more than 21% compared to the conventional adiabatic compressed air energy storage system. Meanwhile, a parametric analysis is also carried out to evaluate the effects of several key parameters on the system performance of the proposed adiabatic compressed air energy storage system.